Precipitation patterns in Usumacinta and Grijalva Basins (southern Mexico) under a changing climate - Andrade-Velázquez, M.; Medrano-Pérez, O. R. (Revista Bio Ciencias, 2020)
The Usumacinta and Grijalva basins of Mexico are characterized by water and natural wealth. This contributes much to their biodiversity and to 30% of the total runoff of Mexico. However, southeastern Mexico is recognized to have great socioeconomic vulnerability and climatic risk. Thus, although in the tropics climatic data are lacking for climate knowledge and understanding, it is essential to analyze precipitation pattern change, because this represents a critical climate variable. The present study analyses the behavior of those patterns using the Standardized Precipitation Index for the period 1960–2016 in the Grijalva and Usumacinta basins. It confirms that wet events occur during negative phases of the Pacific Decadal Oscillation and El Niño/Southern Oscillation, whereas dry events occur in their positive phases. The basins have been subject to different environmental degradation processes, observed to greater or lesser extent in each of the watersheds and parts of the countries involved. Thereby, climate change has put pressure on the natural resources of the area. This is because, among other things, there has been intense degradation of vegetation cover and deforestation. This pressure can be exacerbated by the effects of climate change.